Whole exome sequencing analysis in a couple with three children who died prematurely due to carnitine-acylcarnitine translocase deficiency - Van Khanh Tran; Quang Minh Diep; Zilong Qiu; Thi Phuong Le; Long Duy Do; Hai Anh Tran; The-Hung Bui; Thanh Van Ta; Thinh Huy Tran (Elsevier, 2022)
Objective: We investigated a strategy of exome sequencing DNA from the unaffected parents and applied a set of filtering criteria to identify genes where both partners are heterozygous for a potentially pathogenic variant. Case report: We report a non-consanguineous couple who had three daughters, all spontaneous preterm birth at 36 weeks gestation and died in the first period after birth, suspected inborn errors of metabolism. Two days after birth, the first daughter presented with difficulty breathing, cyanosis and died; the second died at 33 days old; the third daughter was isolated under special care and was taken to the mother's room, developed the same symptoms and died after 5 days. Dried blood spot testing screen of 55 congenital metabolic disorders was negative. Conclusion: Heterogenous variant in SLC25A20 gene was found in both parents, contributing to the delineations of the neonatal phenotypes related to SLC25A20 mutation in CACTD.